Predicting Factors of Health Promoting Behaviors to Preventive Environmental Lung Diseases among Motorcycle Taxi Drivers in Bangkok Metropolitan Area - Suebsuk, Pannipa; Pongnumkul, Autchariya; Sareewiwatthana, Penchun (Nursing Science Journal of Thailand, 2013)
Purpose: This study aimed to examine predicting factors of health promoting behaviors to preventive environmental lung diseases among motorcycle taxi drivers in the Bangkok Metropolitan Area. Design: A correlational predictive design. Methods: The samples included 369 motorcycle taxi drivers in Bangkok Metropolitan Area, Thailand. Data were collected using self-administered questionnaires, including demographicinformation, health promoting behaviors to preventive environmental lung diseases, perceived benefits, perceived self-efficacy, perceived barriers, and the pulmonary function record. Data were analyzed using descriptive statistics, Pearson’s product moment correlation, and multiple regression analysis. Main findings: The samples demonstrated pulmonary function disorders 14.3 %. The majority had a moderate level of health promoting behaviors to preventive environmental lung diseases (84 %). Age, perceived benefits and perceived self-efficacy were significantly positively correlated with health promoting behaviors to preventive environmental lung diseases (r = .141, p < .01; r = .260, p < .01; r = .511, p < .01, respectively). Perceived barriers had a significantly negative relationship with health promoting behaviors to preventive environmental lung diseases (r = - .371, p < .01). Age, perceived benefits, perceived barriers and perceived self-efficacy were significant predictors of health promoting behaviors to preventive environmental lung diseases (β = .091, p < .05; β = .146, p < .001; β = - .448, p < .001; β = .581, p < .001, respectively). Conclusion and recommendations: Health care providers should be proactive in conducting a program providing knowledge and advice regarding the health promoting behaviors to prevent environmental lung diseases, as well as activities that help enhance self-efficacy among motorcycle taxi drivers. This program will benefit this group of population to have appropriate and consistent health promoting behaviors. Keywords: health promoting behaviors, preventive environmental lung diseases, motorcycle taxi บทคัดย่อ วัตถุประสงค์: เพื่อศึกษาปัจจัยทำนายพฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อมของผู้ประกอบอาชีพขับมอเตอร์ไซค์รับจ้าง รูปแบบการวิจัย: การวิจัยหาความสัมพันธ์เชิงทำนาย วิธีการดำเนินการวิจัย: กลุ่มตัวอย่างคือผู้ประกอบอาชีพขับมอเตอร์ไซค์รับจ้าง ในเขตกรุงเทพมหานคร จำนวน 369 คน เครื่องมือที่ใช้ในการวิจัย ได้แก่แบบสอบถามเกี่ยวกับข้อมูลส่วนบุคคล พฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อม การรับรู้ประโยชน์ การรับรู้อุปสรรค การรับรู้สมรรถนะของตนเอง และแบบบันทึกการตรวจสมรรถภาพปอด วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา การวิเคราะห์สหสัมพันธ์แบบเพียร์สัน และการวิเคราะห์ถดถอยพหูคูณ ผลการวิจัย: กลุ่มตัวอย่างมีสมรรถภาพปอดผิดปกติร้อยละ 14.3 ส่วนใหญ่มีพฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อมโดยรวมอยู่ในระดับปานกลาง คิดเป็นร้อยละ 84 อายุ การรับรู้ประโยชน์ และการรับรู้สมรรถนะของตนเอง มีความสัมพันธ์ทางบวกอย่างมีนัยสำคัญทางสถิติกับการปฏิบัติพฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อม (r = .141, p < .01; r = .260, p < .01; r = .511, p < .01 ตามลำดับ) การรับรู้อุปสรรคมีความสัมพันธ์ทางลบอย่างมีนัยสำคัญกับพฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อม (r = - .371, p < . 01) ปัจจัยที่สามารถทำนายพฤติกรรมส่งเสริมสุขภาพ ในการป้องกันโรคปอดจากสิ่งแวดล้อมอย่างมีนัยสำคัญทางสถิติ ได้แก่ อายุ การรับรู้ประโยชน์ การรับรู้อุปสรรค และการรับรู้สมรรถนะของตนเอง (β = .091, p < .05; β = .146, p < .001; β = - .448, p < .001; β = .581, p < .001 ตามลำดับ) สรุปและข้อเสนอแนะ: บุคลากรทางสุขภาพควรจัดกิจกรรมเชิงรุกด้วยการจัดโปรแกรมให้ความรู้ และคำแนะนำเกี่ยวกับพฤติกรรมส่งเสริมสุขภาพเพื่อป้องกันโรคปอดจากสิ่งแวดล้อม และจัดกิจกรรมส่งเสริมการรับรู้สมรรถนะของตนเองแก่ผู้ประกอบอาชีพมอเตอร์ไซค์รับจ้าง เพื่อให้มีการปฏิบัติพฤติกรรมส่งเสริมสุขภาพที่เหมาะสมและสม่ำเสมอในประชากรกลุ่มนี้ คำสำคัญ: พฤติกรรมส่งเสริมสุขภาพ, การป้องโรคปอดจากสิ่งแวดล้อม, มอเตอร์ไซค์รับจ้าง